New Extraction Procedure and Differential Pulse Voltammetric Method for Determination of Water Soluble Chromium(VI) Content in Portland Cement Products - Jaroon Junsomboon (Science Faculty of Chiang Mai University, 2020)
A new extraction procedure employing an off-line extraction column was proposed for the extraction of water soluble chromium(VI) from Portland cement products. A plastic syringe was used as a column by fitting at the bottom with cotton wool and a piece of filter paper to support a cement sample. Deionized water was used to extract the sample under gravity flow, and the eluate was collected for further differential pulse voltammetric (DPV) determination of Cr(VI) in the extract. The extracted solution was placed in a voltammetric cell, added with ammonium tartrate electrolyte solution (0.1 M, pH 9.0), stirred at 2000 rpm, and purged with nitrogen gas for 3 min. Then, the DPV waveform was cathodically scanned to a hanging mercury drop electrode (HMDE) from 0.0 to -0.32 V versus Ag/AgCl reference electrode and a voltammogram was recorded. Peak current of Cr(VI) reduction was measured at a peak potential of -0.16 V. Relative standard deviation for 10 replicate determinations of 100 μg/L of Cr(VI) was 0.87%. Percentage recovery obtained by spiking 40 μg/L Cr(VI) to the sample solution was found to be 98%, and a detection limit of 2 μg/L was achieved. The developed method was applied to the analysis of Portland cement samples by using standard addition procedure. The water soluble Cr(VI) contents in cement which obtained from the column extraction procedure were well correlated with those obtained by the steady state extraction procedure, but it showed slightly higher extraction efficiency. Keywords: differential pulse voltammetry, chromium(VI), portland cement, column extraction